Wonders of the world - Forty, Sandra (TAJ Books International, 2012)
"Wonders of the World sets out to put a wider choice of wonders--ancient and modern--from all around the world, Africa, Asia, Europe, North and Sout America, Oceania. And what a collection it is! From Ayers Rock to the Amazon, from the Wailing Wall to the Great Wall of China, from the Sears Tower to the Petronas Towes, here are 71 of the most impressive, most awe-inspiring, and most beautiful wonders of our world."--Book jacket.